Comparison of clinical effectiveness between tissue adhesives and sutures for wound closure in periodontal flap surgery: a systematic review and meta-analysis - Jeevitha, M.; Kaarthikeyan, Gurumoorthy; Natarajan, Prabhu Manickam (Frontiers in Oral Health, 2025)
BackgroundAlthough traditional sutures are efficient, they can result in complications such as infection and scarring. On the other hand, tissue adhesives have the potential to provide advantages such as reduced application time and postoperative pain. Understanding the comparative outcomes of various procedures can have a substantial impact on clinical periodontal surgery. This systematic review and meta-analysis (PROSPERO CRD42023444615) is designed to synthesize existing research and provide insights into optimizing wound closure procedures for better patient outcomes. The aim of the present systematic review and meta-analysis is to compare the efficacy of tissue adhesives with sutures on wound healing in periodontal flap surgery.Materials and methodsBy adhering to PRISMA 2020 standards, the review outlined systematic processes for identifying and selecting relevant studies, which involved an extensive search across databases such as PubMed, Cochrane Library, Embase, Scopus, Web of Science, Google Scholar, and trial registries. The inclusion criteria focused on all prospective human trials conducted between January 2013 and June 2023, allowing for a diverse range of study designs, including randomized controlled trials, clinical trials, non-randomized trials, and split-mouth trials. Ultimately, 10 and 8 studies were included for qualitative synthesis and quantitative analysis, respectively, with data on the degree of wound closure/healing aggregated from studies that shared similar follow-up periods. Forest plots were created appropriately allowing for a clearer interpretation of the comparative outcomes between tissue adhesives and sutures.ResultsThe assessment of the included studies revealed that most demonstrated a low risk of bias in their methodologies, indicating reliable and robust research practices. However, the forest plot analysis indicated no significant mean difference in the degree of wound healing between tissue adhesives and sutures, despite a high level of heterogeneity (I2 = 94%), suggesting variability in the results among the studies. The funnel plot showed the presence of publication bias with a high standard error.ConclusionWound healing with tissue adhesives appears to be better or comparable to that of sutures in periodontal flap surgery. Tissue adhesives may be a non-invasive alternative to sutures in terms of cosmetic outcome and patient satisfaction. Further randomized trials with larger samples and following standard protocols should be undertaken for their clinical use in periodontal flap surgery.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023444615, PROSPERO CRD42023444615.